Narcissistic Behavior Madrasah Aliyah students on Tiktok - Rahmawati, Novi; Magfiroh, Nafilah; Laksana, Eko (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
Tiktok is one of the most popular social media. On use Tiktok, can function as an educational and entertainment medium, but can also spread misleading value. In Indonesia, existence Tiktok is quite popular, there are around 22.2 million monthly active users. The research aims to determine the level of narcissism of Madrasah Aliyah students who use Tiktok. Researchers used online surveys to collect data. One hundred students using TikTok answered a survey that was launched using a Google form. Overall, the results show that student narcissism is at a moderate level. In detail, 34 students have narcissistic behavior at a low level, 31 students are in the very low category, 28 students are moderate, and 7 students are in the high category, these students have a tendency to use Tiktok only to access entertainment.